Pengaruh Tingkat Pendidikan dan Disiplin Kerja terhadap Kinerja Karyawan di The Udaya Resort and Spa Ubud - Wirata, Ni Made Arwita Sari; Subadra, I Nengah (Jurnal Mosaik Hospitaliti, 2023)
This study aims to analyze the effect of education level and work discipline on employee performance partially and simultaneously. This study uses a quantitative research design with the variables studied: education level, work discipline, and employee performance. The research subjects used all 43 employees who worked at The Udaya Resort & Spa Ubud, which it was called a saturated sample population study. The data collected in this study is the level of education, work discipline, and employee performance. Data were collected by using questionnaires and observation techniques which were then analyzed using multiple linear regression analysis techniques. The analysis results show that (1) education level partially has a positive and significant effect on employee performance at The Udaya Resort & Spa Ubud which is indicated by the results of the regression coefficient b1x1 which is positive. (2) work discipline has a positive and significant effect on employee performance at The Udaya Resort & Spa Ubud, this can be seen from the results of the b2x2 positive regression coefficient. (3) education level and work discipline have a positive and significant effect on employee performance at The Udaya Resort & Spa Ubud.